Unusual alleles of recB and recC stimulate excision of inverted repeat transposons Tn10 and Tn5. - Lundblad, V (1984)
Precise and nearly precise excision of transposon Tn10 occur by host-mediated processes unrelated to transposition. Both types of excision involve interactions between short (9 or 24 base-pair) direct repeat sequences at or near the termini of the transposon and are stimulated by the large (1,329-base-pair) inverted repeats that form the ends of Tn10. We describe here three mutations of Escherichia coli K-12, designated texA, that enhance excision of Tn10 and of the structurally analogous transposon Tn5. Genetic mapping and complementation analysis show that these mutations are unusual alleles of the recB and recC genes that alter but do not abolish RecBC function. As Tn10 excision normally does not depend on RecA or RecBC functions, texA mutations appear to provide another pathway for excision that depends on altered RecBC function; for one texA allele, excision has become dependent on RecA function as well. The available evidence suggests that texA mutations alter the stimulatory interaction between the inverted repeats of Tn10.